Sosialisasi Pentingnya Uji Laboratorium Material Bangunan Pra Pembangunan di Desa Cabean, Kecamatan Sawahan, Kabupaten Madiun - Rochidajah Rochidajah; Rendi Gusta Wibowo (JURNAL DAYA-MAS, 2019)
Indonesia is a country that is carrying out development with a large population. The construction of citizen housing has occurred in many regions. But many homes were damaged. One reason is the use of building materials. Each construction must be subjected to material testing first. One material that is usually tested is concrete. Concrete testing can be done including the Specific Gravity Test and Absorption of Coarse Aggregate Water, as well as the Content Weight Test, Mixed Production Volume, and Concrete Air Content. In this service activity, socialization will be carried out to the public about the importance of testing building materials before carrying out construction. Because some people still have not tested material before carrying out construction. The activities carried out included socialization, training, and mentoring. After the activity is complete, an understanding evaluation of the material is carried out. From the results of the evaluation, it was found that the percentage of understanding was 53%, for the people who understood enough by 31%, and those who did not understand at 16%.